Perfil de compostos bioativos e volátil dos pós de jamelão (Syzygium cumini) obtidos por diferentes métodos de desidratação - Almeida, Christian Alley de Aragão (2019)
Jambolan (Syzigium cumini L.) is a fruit harvested from January to May and has a high productivity. For a better use of this rich fruit in health benefits, compounds with exotic and smooth aroma and flavor, it is necessary to apply processes that increase shelf life and preserve its characteristics, minimizing the loss of its benefits. The goal was to obtain the dehydrated powder from pulp/juice of jambolan through different dehydration methods, such as freeze drying, convective drying and the spray drying process, characterize them physicochemically, quantify their bioactive compounds in LC-MS and identify their volatile compositions in GC-MS. The pulp contained 73,25 mg GAE/100 g of phenolic compounds, 14,01 mg QE/100 g of total flavonoids and 5762 mg 3-cy-gicoside/100 g of total anthocyanins. It also showed good antioxidant activity (DPPH – 255,2 μmol TE/g, ABTS - 2944,5 μmol TE/g and FRAP - 2952,17 μmol Fe 2+/g). There was na increase in the concentration of total phenolics, flavonoids and anthocyanins in the freeze-dried powder, with this increase in antioxidant activity (977,4 mg GAE/100 g of phenolic compounds, 443,1 mg QE/100 g of total flavonoids and 1116,4 gt; 3-cy-gicoside/100 g, DPPH – 395,25 μmol TE/g, ABTS – 3331,5 μmol TE/g and FRAP – 5311,11 μmol Fe2+ / g). The dehydrated powders obtained in the convective dryer, at temperatures of 40, 50 and 60 ⁰C, presented a reduction of these compounds, as well as their respective antioxidant activities. Among the samples dehydrated in the convective dryer, the 40 ⁰C showed the best results (203,6 mg GAE/100 g phenolic compounds, 51,05 mg QE/100 g total flavonoids and 766,9 mg 3-cy-gicoside/100 g, DPPH – 189,5 μmol TE/g, ABTS – 641,17 μmol TE/g and FRAP – 656,8 μmol Fe2+/g). In the optimization of the spray dryer process, just the a* coordinate, chroma, efficiency, total phenolics, anthocyanins, turbidity, wettability, water solubility index and water absorption index were influenced by the independent variables. The predictive model of the Desirability function generated was 17,3% maltodextrin and 155 °C. In the validation, the actual values of the dependent variables showed a low coefficient of variation, confirming the prediction of the model. Gallic acid and catechin were the most important compounds in all samples, with fresh pulp having the highest bioactive contents, followed by freeze-dried powder, convective-dried powder at 40 °C and dehydrated powder obtained from juice at optimized conditions in spray dryer. The volatile composition of the pulp and its dehydrated products showed that the terpene class is the one with the highest percentage of compounds. The concomitant volatile compounds in the pulp and its dehydrated products were: D-limonene, copaene, caryophyllene, humulene, γ-muurolene and α-terpineol. Only the dehydrated powder obtained from juice in spray dryer had furan compounds, which are formed by thermal induction. Therefore, it is noticed that both the pulp of jambolan and its dehydrated products are rich sources of bioactive compounds, with significant antioxidant activity. The dried powders produced were able to preserve some volatile compounds present in the pulp, thus approaching its aroma and flavor characteristic of fresh jambolan.